A longitudinal mass transfer barrier high-concentration micro direct methanol fuel cell
Patent Information
- Application Number
- CN202210259364.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-16
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-03-16
AI Technical Summary
被动式μDMFC阳极反应物的传质以浓差扩散的方式,横向扩散穿过各层抵达催化层参与氧化反应,这种横向构型很难在有限的层厚度间将甲醇浓差梯度拉开,这也很大程度的降低了传质阻挡的效果
[0026]与现有技术相比,本发明具有以下有益效果:本发明利用不锈钢纤维毡(stainless steel fiber felt,SSFF)的材料特性,结合有限元仿真和表面浸润性改性处理,设计并制备了适合高甲醇浓度工况的纵向传质阻挡微型直接甲醇燃料电池(VerticalMass Transfer BarrierμDMFC,VMTB-μDMFC)。电化学实验结果表明,在298K温度及其他最优参数下,VMTB-μDMFC较传统μDMFC的最优燃料浓度提升至7M;最大功率密度提升了56%,单位体积高浓度燃料的放电时长提升了148%;在333K温度下最大功率密度提升了83%。VMTB-μDMFC更小的阴极内阻和更低的甲醇渗透LSV峰值,证明其因为甲醇渗透降低所带来的输出性能提升。综上所述,纵向传质阻挡结构能有效减少高浓度工况下的甲醇渗透,使VMTB-μDMFC能在高浓度环境下具备更好的输出性能和更长的放电时间。
Smart Images

Figure CN116799245B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of direct methanol fuel cells, and more particularly to a micro direct methanol fuel cell with a high concentration of longitudinal mass transfer barrier layer. Background Technology
[0002] As portable electronic devices are increasingly used in both military and civilian fields, their functions are becoming more diverse, leading to a surge in power consumption. This has created a growing demand for portable power sources capable of continuous, stable, and high-power output. Passive micro direct methanol fuel cells (μDMFCs), as a highly efficient and clean new energy technology, boast high energy conversion efficiency, with both the energy carrier and byproducts being renewable and environmentally friendly resources. Due to their elimination of the need for an external fuel supply system and their advantages of system simplicity, small size, light weight, and ease of integration, they are widely recognized as one of the most promising alternatives to traditional power sources for portable and mobile applications.
[0003] Passive μDMFCs use high-concentration methanol fuel, which helps improve the fuel's energy-to-volume ratio, thereby increasing battery capacity and driving range. However, this also brings significant negative impacts. High-concentration methanol solutions can easily diffuse and electromigrate through the hydrated proton exchange membrane to the cathode (leading to a decrease in battery performance). The permeated methanol creates a mixed potential under the catalysis of the cathode Pt catalyst, eroding the reaction sites of the cathode catalyst Pt. The intermediate product CO from the cathode oxidation of methanol poisons the cathode catalyst. Large amounts of methanol solution permeating into the cathode also prevent the contact between the cathode reactant O2 and the catalyst, further reducing the three-phase interface for the cathode oxygen reduction reaction, and also lowering fuel utilization. Many studies have shown that the optimal fuel concentration for passive μDMFCs is generally 2M, with concentrations exceeding 5M considered high. Currently, there are three main technical approaches to address the methanol permeation problem of high-concentration fuels. The first approach involves material treatment on the proton exchange membrane to reduce methanol permeability, but this also reduces proton conductivity, making it difficult to achieve a balance between proton conductivity and methanol permeability. The second method uses methanol vapor as fuel, which can effectively reduce methanol permeation and enable operation in high-concentration solutions. The third approach involves establishing a mass transfer barrier layer between methanol and the proton exchange membrane, creating a concentration gradient of methanol within the barrier layer; this is currently a major research direction for reducing methanol permeation. Porous metals and metal fiber felts possess high porosity and excellent electrical conductivity, which aligns with the material properties of passive μDMFC mass transfer layers.
[0004] Currently, research on porous metal or metal fiber felt as mass transfer barrier layers mainly focuses on lateral structures, where the fuel chamber, manifold, mass transfer barrier layer, and catalyst layer are at the same horizontal level. In passive μDMFC, the mass transfer of the anode reactants occurs via concentration gradient diffusion, which diffuses laterally through each layer to reach the catalyst layer and participate in the oxidation reaction. This lateral configuration makes it difficult to create a methanol concentration gradient within the limited layer thickness, which significantly reduces the effectiveness of the mass transfer barrier. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a high-concentration micro direct methanol fuel cell with a vertical mass transfer barrier layer. Utilizing the capillary force of a porous stainless steel fiber felt (SSFF) structure, combined with finite element numerical simulation results of methanol diffusion, this invention designs a vertical mass transfer barrier micro direct methanol fuel cell (VMTB-μDMFC). Chemical etching is used to increase the surface roughness of the stainless steel fiber felt (SSFF), thereby increasing the capillary pressure difference in the pores. This satisfies the material requirements of VMTB-μDMFC for bottom-up transport of methanol solution within the vertical mass transfer barrier layer (VMTB-Layer).
[0006] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: A high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer includes an anode end plate and a cathode end plate as clamps. A liquid storage chamber is provided inside the lower part of the anode end plate. One side of the liquid storage chamber is sealed by a longitudinal mass transfer barrier layer and an anode sealing gasket. The longitudinal mass transfer barrier layer is embedded in one side of the anode sealing gasket and is in contact with the MEA (membrane electrode). The other side of the MEA is in contact with the cathode current collector through the cathode sealing gasket. A cathode end plate is provided outside the cathode sealing gasket and the cathode current collector.
[0007] Preferably, the longitudinal mass transfer barrier layer is made of stainless steel fiber felt material with a porosity of 70%-90%, which conducts the methanol solution from the reservoir on one side to the MEA anode diffusion layer on the other side through capillary pressure difference. More preferably, the porosity is 80%.
[0008] Preferably, the surface of the stainless steel fiber felt is chemically etched to form a microstructure, thereby improving the surface roughness. The process is as follows: the stainless steel fiber felt is immersed in a mixed solution of CuCl2 and HCl and reacted at 45-55℃ for 25-35 seconds. Then, it is immediately ultrasonically cleaned for 10-20 minutes to remove the Cu deposited on the fiber surface, and then dried in a constant temperature oven.
[0009] Furthermore, a cuboid frame is formed in the middle of the anode sealing gasket, a longitudinal mass transfer barrier layer is embedded on one side of the cuboid frame, and an anode diffusion layer of the MEA is embedded on the other side of the cuboid frame, with the anode diffusion layer of the MEA in contact with the longitudinal mass transfer barrier layer.
[0010] Furthermore, the liquid storage chamber is connected to a fuel filling channel, the opening of which is located above the anode end plate.
[0011] Furthermore, the MEA has a proton exchange membrane in the middle, an anode diffusion layer on the left, and a cathode diffusion layer on the right. The anode diffusion layer is coated with an anode catalyst on the side close to the proton exchange membrane, and the cathode diffusion layer is coated with a cathode catalyst on the side close to the proton exchange membrane.
[0012] Furthermore, the cathode current collector is a 304 stainless steel current collector with an opening ratio of 38.5%, which has excellent corrosion resistance, conductivity and high mechanical strength, providing conditions for clamping the MEA in the charge transfer and encapsulation process.
[0013] Preferably, the methanol fuel cell has a fuel concentration of 5-8 M; more preferably, the methanol fuel cell has a fuel concentration of 7 M.
[0014] Preferably, the lower edge of the anode diffusion layer of the MEA is 3-10 mm away from the upper edge of the liquid storage cavity. This range is designed to ensure sufficient mass transfer barrier distance, without obstructing the longitudinal transport of the solution to the MEA, and to ensure that the battery has a small volume. The width of the longitudinal mass transfer barrier layer is consistent with the width of the MEA.
[0015] Preferably, the bottom end of the longitudinal mass transfer barrier layer coincides with the lower edge of the liquid storage cavity, and the top end is 3-10mm higher than the top end of the anode plate. This design is based on the need for the longitudinal mass transfer barrier layer to act as an electrode to conduct charge, so it needs to be longer than the top end of the plate.
[0016] The parameters of each structure in this invention are as follows: the anode end plate is 40×40×15mm. 3 Made of acrylic sheet, with a 20×5×10mm engraving cut out 30mm below the top. 3The container has a rectangular liquid storage cavity. A 2mm diameter injection channel is machined from the top into the liquid storage cavity. 4mm diameter screw holes are provided at the four corners for sealing.
[0017] The longitudinal mass transfer barrier layer has dimensions of 10×40×0.6mm. 3 The stainless steel fiber felt has a porosity of 80% and has undergone chemical etching treatment. Its bottom end coincides with the lower edge of the liquid storage cavity, and its top end is 3-10 mm higher than the top of the anode end plate.
[0018] The area of the inner diffusion layer and catalyst layer of MEA4 is (10×10 mm) 2 The finite area of the intermediate proton exchange membrane is (1.4 × 1.4 mm). 2 The MEA is positioned on the cathode side of the longitudinal mass transfer barrier layer, above the reservoir. The lower edge of the diffusion layer of the anode inside the MEA is 3-10 mm away from the upper edge of the reservoir, and it contacts the longitudinal mass transfer barrier layer through the anode sealing gasket.
[0019] The thickness of the anode sealing gasket is 0.6-0.8mm, and it has a 10×35mm opening. 2 The rectangular frame embeds the longitudinal mass transfer barrier layer inside.
[0020] The thickness of the cathode sealing gasket is 1.5-1.7mm. A retaining frame is made according to the cathode current collector to fit the cathode current collector inside.
[0021] The cathode current collector is 1.5 mm thick, with a 1 mm diameter hole and an opening ratio of 38.5%.
[0022] The dimensions of the cathode end plate are (40×40×5mm) 3 ), and has a 10×10mm in the center. 2 A square opening.
[0023] Designing the battery structure according to the above parameters can effectively reduce methanol permeation under high concentration conditions, enabling VMTB-μDMFC to have better output performance and longer discharge time in high concentration environments.
[0024] The features of this invention are as follows: Based on the working principle and structural basis of the traditional μDMFC structure, this invention designs a longitudinal mass transfer barrier structure VMTB-μDMFC, the structure of which is as follows: Figure 1As shown. The components and their functions in this structure, from left to right, are as follows: (1) Anode end plate: as part of the clamp, it provides pressure for battery encapsulation and has a liquid storage chamber and fuel filling channel inside to store methanol fuel for the battery; (2) Longitudinal mass transfer barrier layer: it transfers the methanol solution from the liquid storage chamber below to the MEA (membrane electrode) above, the charge generated by the reaction is transferred to the external circuit through it, and the product gas is discharged from the battery from the top, which works with the anode and cathode end plates and the cathode current collector to clamp the MEA; (3) Sealing gasket: it works with the MEA to block the reactants at both electrodes, and the anode sealing gasket can prevent methanol solution leakage; (4) MEA4: it undergoes redox reaction and generates electrical energy; (5) Cathode current collector: it introduces oxygen into the MEA cathode, conducts charge to the cathode catalyst layer, and works with the end plate and barrier layer to provide clamping force for the MEA; (6) Cathode end plate: it provides the pressure required for encapsulation.
[0025] The main difference between this invention and traditional structures lies in the anode section. Based on the principle of mass transfer barrier, a longitudinal mass transfer barrier layer (VMTB-Layer) needs to be established between the anode fuel inlet (i.e., the reservoir) and the MEA, connecting the two. The longitudinal mass transfer barrier structure still satisfies this structural characteristic, but the reservoir is not horizontally connected to the MEA at the same level; instead, it is positioned below the MEA membrane, with the solution being transported upwards to the MEA through the VMTB-Layer. The purpose of placing the reservoir below is to allow the gaseous products generated by the anode reaction to spontaneously exit the battery through the pores above the VMTB-Layer, thereby reducing the obstruction to gaseous product emission. Because the VMTB-Layer in this structure not only needs to act as an alcohol barrier but also needs to perform functions such as solution transport and electronic conduction, this invention selects a porous metal material as the VMTB-Layer. The reasons for this selection are as follows: the porous structure of the material is conducive to the transport of the solution within it; its excellent metallic conductivity can replace the anode current collector to conduct charge to the external circuit, reducing the number of anode structural components and lowering the complexity; it can have a high porosity to facilitate the emission of gaseous products; and it has good mechanical strength to provide sufficient clamping force to the MEA.
[0026] Compared with existing technologies, this invention has the following advantages: Utilizing the material properties of stainless steel fiber felt (SSFF), combined with finite element simulation and surface wettability modification, this invention designs and fabricates a vertical mass transfer barrier micro direct methanol fuel cell (VMTB-μDMFC) suitable for high methanol concentration conditions. Electrochemical experimental results show that, at 298K temperature and other optimal parameters, the VMTB-μDMFC achieves an optimal fuel concentration of 7M compared to the traditional μDMFC; the maximum power density is increased by 56%, and the discharge time per unit volume of high-concentration fuel is increased by 148%; the maximum power density is increased by 83% at 333K temperature. The VMTB-μDMFC's lower cathode internal resistance and lower methanol permeation LSV peak demonstrate the improved output performance due to reduced methanol permeation. In summary, the vertical mass transfer barrier structure effectively reduces methanol permeation under high concentration conditions, enabling the VMTB-μDMFC to have better output performance and a longer discharge time in high-concentration environments. Attached Figure Description
[0027] Figure 1 Exploded view of the structure of a high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer;
[0028] Figure 2 This is a schematic diagram of a high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer.
[0029] Figure 3 This is a schematic diagram of the MEA structure;
[0030] Figure 4 These are the theoretical values of permeability under different porosities;
[0031] Figure 5 This is a diagram showing the concentration distribution of methanol within the VMTB-Layer and the diffusion layer;
[0032] Figure 6 This is a graph showing the internal methanol concentration distribution of the catalyst layer in the VMTB-Layer under different porosities;
[0033] Figure 7 The images show the surface morphology of SSFF fibers obtained by SEM scanning. (a) is before chemical etching, and (b) is after chemical etching.
[0034] Figure 8 This is a dynamic contact angle measurement diagram;
[0035] Figure 9 The graphs show the polarization curve and power output curve.
[0036] Figure 10 The following are polarization curves: (a) polarization curve at room temperature (298 K); (b) polarization curve at high temperature (333 K).
[0037] Figure 11 The long-term discharge test curve is used to test the stability of discharge and the battery life.
[0038] Figure 12 Nyquist plot of AC impedance spectrum;
[0039] Figure 13 EIS equivalent circuit diagram;
[0040] Figure 14 LSV scan curves of methanol permeation at 298 K and 333 K for VMTB-μDMFC and conventional μDMFC;
[0041] The markings in the diagram are: 1-anode end plate, 2-longitudinal mass transfer barrier layer, 3-anode sealing gasket, 4-MEA, 5-cathode sealing gasket, 6-cathode current collector, 7-cathode end plate, 8-liquid storage chamber, 9-channel. Detailed Implementation
[0042] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the present invention is not limited to the following technical solutions.
[0043] Example 1
[0044] like Figure 1 As shown, a high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer includes an anode plate 1 and a cathode plate 7 as clamps. The anode plate 1 has a liquid storage chamber 8 located at its lower interior. The liquid storage chamber 8 is connected to a fuel filling channel 9. The opening of the channel 9 is located above the anode plate 1. Fuel is filled through the channel 9 after the battery is installed.
[0045] The liquid storage chamber 8 has an opening on one side and is sealed by a longitudinal mass transfer barrier layer 2 and an anode sealing gasket 3. A cuboid frame is formed in the middle of the anode sealing gasket 3. The longitudinal mass transfer barrier layer 2 is fitted into one side of the cuboid frame, and the anode diffusion layer of MEA4 is fitted into the other side of the cuboid frame. The anode diffusion layer of MEA4 is in contact with the longitudinal mass transfer barrier layer 2. The liquid storage chamber 8 is sealed by the longitudinal mass transfer barrier layer 2 and the anode sealing gasket.
[0046] A frame is opened inside the cathode sealing gasket 5. The shape and size of the frame match the cathode current collector 6. The cathode diffusion layer of MEA4 contacts the cathode current collector 6 after passing through the frame. An opening is made in the middle of the cathode end plate 7. The other side of the cathode current collector 6 is exposed through the opening on the cathode end plate 7.
[0047] In this embodiment, the longitudinal mass transfer barrier layer 2 is made of 304 stainless steel fiber felt with a porosity of 70%-90%. The stainless steel fiber felt conducts the methanol solution from the reservoir 8 on one side below to the MEA4 anode diffusion layer on the other side above through capillary pressure difference. Its excellent metallic conductivity can replace the anode current collector to draw out electrons, reducing the anode structure and lowering the internal contact resistance. The cathode current collector uses a 304 stainless steel current collector with a porosity of 38.5% to provide sufficient conductivity and support.
[0048] The surface of the stainless steel fiber felt is chemically etched to form a microstructure, which improves the surface roughness. The process is as follows: the stainless steel fiber felt is immersed in a mixed solution of CuCl2 and HCl and reacted at 45-55℃ for 25-35 seconds. Then, it is immediately ultrasonically cleaned for 10-20 minutes to remove the Cu element deposited on the surface of the fiber. Finally, it is dried in a constant temperature oven.
[0049] The anode and cathode end plates are machined from 40×40×15mm and 40×40×5mm acrylic sheets, respectively. A 20×5×10mm reservoir is milled into the lower half of the anode end plate for fuel filling and volume measurement. A sealing gasket is inserted between the end plate and the MEA assembly to prevent methanol solution leakage. During installation, the anode end plate 1, anode sealing gasket 3, cathode sealing gasket 5, and cathode end plate 7 are secured with screws at the four corners.
[0050] The MEA (10×10mm) was formed by hot pressing at 18MPa and 135℃ after preparing the following five functional layers. A slurry of a mixture of PTFE (10wt.%) and toner was coated onto carbon paper (TGPH-090, Toray Inc.) and baked at high temperature to form an anode diffusion layer and a cathode diffusion layer (ADL, CDL) with a microporous substrate. An anode catalyst (Pt+Ru(60%), C(40%)) and a cathode catalyst (Pt(40%), C(60%)) were coated on the side of the diffusion layer near the proton exchange membrane, with loadings of 4 mg / cm³, respectively. 2 and 2mg / cm 2 To form a catalyst layer. The proton exchange membrane in the middle is made of Nafion 115 (DuPont) and hot-pressed.
[0051] The specific parameters of each structure in this embodiment are as follows: The male end plate 1 is made of acrylic and is milled with a diameter of 20×5×10mm at a distance of 30mm below the top. 3 The container has a rectangular liquid storage cavity 8. A liquid injection channel with a diameter of 2mm is machined from the top into the liquid storage cavity. Screw holes with a diameter of 4mm are provided at the four corners for sealing.
[0052] The longitudinal mass transfer barrier layer 2 has dimensions of (10×40×0.6mm).3 The stainless steel fiber felt has a porosity of 80% and has undergone chemical etching treatment. Its bottom end coincides with the lower edge of the liquid storage cavity 8, and its top end is 5mm higher than the top end of the anode plate 1.
[0053] The area of the inner diffusion layer and catalyst layer of MEA4 is (10×10 mm) 2 The finite area of the intermediate proton exchange membrane is (1.4 × 1.4 mm). 2 The MEA4 is positioned on the cathode side of the longitudinal mass transfer barrier layer 2, above the liquid storage chamber 8. The lower edge of the diffusion layer of the anode inside the MEA4 is 5 mm away from the upper edge of the liquid storage chamber 8, and it contacts the longitudinal mass transfer barrier layer 2 after passing through the anode sealing gasket 3.
[0054] The thickness of the anode sealing gasket 3 is 0.8mm, and it has an opening of (10×35mm). 2 The rectangular frame encloses the longitudinal mass transfer barrier layer 2 inside.
[0055] The cathode sealing gasket 5 has a thickness of 1.7mm. A frame is made according to the cathode current collector 6 to fit the cathode current collector 6 inside.
[0056] The cathode current collector 6 has a thickness of 1.5 mm, a diameter of 1 mm for the circular holes, and an opening ratio of 38.5%.
[0057] The dimensions of the cathode end plate 7 are (40×40×5mm) 3 ), and has a 10×10mm in the center. 2 A square opening.
[0058] Example 2: VMTB-Layer Design Process
[0059] When selecting the porosity specification for a VMTB-Layer, priority should be given to specifications with higher permeability to facilitate the longitudinal transport of the aqueous solution. The porosity of the fibrous metal significantly affects the permeability of the solution within it. The Kozeny–Carman equation describes the relationship between porosity and permeability coefficient K in porous media as follows:
[0060]
[0061] Where C is the Carman constant, here C = 0.5, ε is the porosity, and d a This is the average equivalent pore size. Substituting the specifications of several commercially available SSFFs with different porosities into Equation 1, we can solve for their permeability coefficients, such as... Figure 4SSFFs with a porosity of 70%–90% exhibit a significantly higher permeability coefficient compared to SSFFs with other porosities. Therefore, SSFFs within this porosity range are preferred for methanol diffusion simulation analysis.
[0062] Methanol diffusion within the VMTB-μDMFC was simulated using the finite element method software COMSOL Multiphysics 5.6. The simulation results were compared to further determine the porosity. In the anode catalyst layer, the methanol flux N... m The governing equations are:
[0063]
[0064] Where i is the anodic oxidation current and F is the Faraday constant. The first term on the right-hand side of the equation represents the consumption of methanol by electro-oxidation, which follows Faraday's law. The second term is the methanol permeation, described as:
[0065]
[0066] In this equation, the first term on the right-hand side is the diffusion term, and the second term is the electroosmosis term of the aqueous solution. It is the effective diffusion coefficient of methanol within the proton exchange membrane. It is the methanol concentration gradient of the anode catalyst layer. It is the electroosmotic coefficient, determined by the following formula:
[0067]
[0068] In the formula, Let x be the electroosmotic coefficient of water. m This represents the molar fraction of methanol and water.
[0069] The flux of methanol diffusing from the VMTB-Layer to the catalyst layer is described as follows:
[0070]
[0071] Where, N m,ADL This represents the methanol flux of ADL. D represents the methanol concentration gradient within the SSFF. ssff Let be the diffusion coefficient of methanol in the mass transfer barrier layer, and D be the diffusion coefficient of methanol in the aqueous solution.
[0072] The computational domain was set to include a VMTB-Layer and a MEA assembly. The anodic oxidation reaction current i was set to 90 mA / cm² to observe mass transfer under high-current discharge conditions. The inlet methanol fuel concentration C was also set. in Simulation results of methanol distribution in VMTB-μDMFC with 70% porosity at 1M, 3M, 5M, 7M, and 9M are shown below. Figure 5 As shown.
[0073] Figure 5 In the process, the concentration distribution of methanol within the VMTB-Layer and the diffusion layer will be affected by C. in The concentration of methanol in the diffusion layer varies significantly depending on the concentration. At high concentrations of 5–9 M, the VMTB-Layer provides significant mass transfer resistance and effectively widens the concentration gradient from bottom to top by utilizing the longer mass transfer distance, thereby reducing the methanol concentration in the diffusion layer. At low concentrations of 1 M and 3 M, methanol diffusion on the VMTB-Layer is hindered, resulting in excessively low methanol concentrations within the diffusion layer.
[0074] In addition to the inlet concentration, the porosity of the VMTB-Layer also affects the transport of methanol to the catalyst layer. Figure 6 VMTB-Layer with 70%, 80%, and 90% porosity in C in The concentration distribution within the catalyst layer under a 7M condition is shown in the simulation results. Lower porosity hinders methanol diffusion, leading to a decrease in methanol concentration within the catalyst layer, while higher porosity has the opposite effect. Therefore, the selection of porosity and the corresponding methanol fuel concentration are crucial for controlling the methanol concentration within the VMTB-μDMFC catalyst layer.
[0075] Traditional μDMFCs achieve optimal performance at 2M. Under these conditions, the average methanol concentration within the anode catalyst layer of a traditional μDMFC is used as a reference standard for the optimal catalyst layer concentration. Inlet methanol concentration C ir Simulations were performed on the anodic diffusion of VMTB-μDMFC with porosities of 70%, 80%, and 90% using a setting of 1–10 M. The average methanol concentration within the catalyst layer was calculated. and By comparison, the optimal porosity was obtained. and its corresponding C in The results are shown in Table 1.
[0076] Table 1. Simulation results of optimal concentration under different porosities
[0077]
[0078] In Table 1, the concentration of the catalyst layer in the VMTB-Layer with 80% porosity at 7M is closest to... Therefore, the methanol concentration in the MEA can be maintained at the optimal operating conditions. Compared to VMTB-Layer with 70% porosity, it has high permeability. Its optimal fuel concentration is also higher than that of 6M with 90% porosity, better demonstrating the advantages of high concentration. In conclusion, SSFF with 80% porosity was ultimately selected for the preparation of VMTB-Layer.
[0079] Example 3: Preparation of VMTB-Layer
[0080] Methanol at the anode is primarily transferred via ion diffusion in aqueous solution. The VMTB-Layer, besides acting as a barrier layer for methanol diffusion, also serves to transport the methanol-water solution, providing a pathway for the longitudinal diffusion of methanol. This relies on the inherent advantage of the capillary pressure difference between the pore structure of the fibrous metal and the aqueous solution. Increasing the capillary pressure difference between the pores of the SSFF can amplify this mass transfer advantage, thereby meeting the requirements of the VMTB-μDMFC for methanol solution transport.
[0081] According to Wenzel's modified equation for Young's equation:
[0082]
[0083] Where θ is the intrinsic contact angle of the material, θ rw To observe the contact angle, r is the surface roughness factor, determined by the ratio of the actual contact area between the solid and the liquid to the area of the liquid's horizontal projection onto the solid surface. The high surface energy of stainless steel contributes to its hydrophilicity, resulting in an intrinsic contact angle θ < 90°. Substituting equation (2) into the Laplance-Young equation to describe the capillary pressure difference of the liquid in the pores of SSFF:
[0084]
[0085] σ is the surface tension of the liquid, r p Let be the equivalent pore radius. Under steady-state conditions, the capillary pressure difference in the vertical direction of the methanol-water solution in the VMTB-Layer is balanced by the hydrostatic pressure generated by gravity, so it will remain stationary at a certain height, i.e.:
[0086]
[0087] Wherein, ΔP cap Let ρ be the capillary pressure difference, ρ be the density of the methanol solution, and h be the static height of the methanol solution in the VMTB-Layer. Increasing the surface roughness, without changing the pore size, is a method to increase the capillary pressure difference and transport the liquid to a higher height.
[0088] Since the unipolar reaction equation at the anode is:
[0089] CH3OH + H2O → 6H + +6e - +CO2 (5)
[0090] After the methanol solution is transported to the upper layer, since water is the anolyte, some of the water in the solution will be consumed in addition to the methanol being reacted. Furthermore, with the generation and desorption of CO2 and the intermediate product CO, a gas phase channel will be generated at the upper end of the VMTB-Layer. At this time, the solution will be continuously drawn from the bottom to the top. Therefore, the dynamic transport of the methanol solution in the VMTB-Layer also needs to be considered, described as follows:
[0091]
[0092] In this equation, the first term on the right-hand side is Darcy's law term, μ is the viscosity of the solution, ε is the porosity, and K is the permeability. The rate of liquid level rise is considered. Dynamically, increasing the surface roughness of the SSFF (Self-Solid Filtered Fluid) to increase the capillary pressure difference, or increasing permeability, can both improve the rate and height of liquid level rise. Without changing the pore size of the selected SSFF, wetting treatment can be applied to the SSFF surface to increase the surface roughness. This is an effective way to allow the solution to be transported to higher positions more quickly under both steady-state and dynamic conditions, thereby providing a stable pathway for the longitudinal diffusion of methanol molecules.
[0093] In this embodiment, a chemical etching method is used to form a microstructure on the surface of SSFF fibers, thereby increasing the surface roughness and modifying its wettability. SSFF of the above specifications is selected and immersed in a mixed solution of CuCl2 (1 mol / L) and HCl (1 mol / L) at 50°C for 30 seconds. Immediately afterwards, it is ultrasonically cleaned for 15 minutes to remove the small amount of elemental Cu deposited on the fiber surface, and then dried in an oven at 80°C for 2 hours.
[0094] Figure 7 The image shows the surface morphology of SSFF fibers obtained by SEM scanning. Figure 7 In (a), before chemical etching, the SSFF surface is smooth with almost no microstructure and low surface roughness. The treated fiber surface is as follows: Figure 7 As shown in (b), etching formed micron-sized stepped corrosion pits on its surface, with fine nanoscale indentations distributed on the surface of the corrosion pits, significantly increasing the surface roughness. The formation process of the microstructure can be attributed to the presence of Cl in the etching solution. - Its small ionic radius allows it to preferentially penetrate and destroy the oxide layer membrane, subsequently causing Cu to... 2+ A displacement reaction occurs at the damaged site upon contact with the iron matrix, generating Fe.2+ After washing away the deposits from the elemental copper, corrosion pits were left on the surface. Due to uneven ion diffusion and other factors, the corrosion rate varied in different areas, leaving nanoscale indentations on the surface of the corrosion pits.
[0095] After chemical etching, the hydrophilicity of SSFF is enhanced by increasing the surface roughness, and the capillary pressure difference is also correspondingly improved. Due to its porous structure, droplets on the surface are rapidly dispersed in all directions under the drive of capillary forces. Figure 8 To record the moment a 5 μL deionized water droplet is dispersed upon contact with the mass transfer barrier layer surface using a contact angle meter (SL200KS) equipped with a high-speed camera, the shooting interval was 22 ms. The results show that after etching, the SSFF can rapidly disperse the droplets on its surface through capillary force within 110 ms, effectively meeting the longitudinal transport requirements of the VMTB-Layer for methanol solutions. Using this as the VMTB-Layer, according to... Figure 1 As shown, the battery is assembled to form a VMTB-μDMFC.
[0096] Example 4 Performance Test
[0097] A 304 stainless steel current collector with an opening ratio of 42% was used to replace the VMTB-Layer in the assembly of a conventional μDMFC without a mass transfer barrier layer, serving as an experimental control. Polarization curves and long-term discharge tests were conducted on the VMTB-μDMFC and the conventional μDMFC at different fuel concentrations and temperatures using an electron load to investigate their mass transfer and output characteristics. Using ZView software, AC impedance spectra obtained from an electrochemical workstation (CHI660E) were fitted to analyze the changes in internal resistance of the anode and cathode under high fuel concentrations. LSV scanning was performed using the electrochemical workstation to reverse-oxidize methanol permeating into the cathode, and the peak values of the curves were measured to characterize the methanol permeation rate.
[0098] Output performance test
[0099] Discharge tests of VMTB-μDMFC with different fuel concentrations were conducted at room temperature (298K). The polarization curves and power output curves are shown below. Figure 9 As shown in the figure. Observation of the curves reveals that the optimal fuel concentration for VMTB-μDMFC is 7M, at a discharge current density of 80 mA / cm². 2 The maximum power density achievable at this time is 16.92 mW / cm³. 2 Under the condition of methanol concentration of 5M, its maximum power density is 14.83 mW / cm³. 2 It appears at 70mA / cm 2At the current density, the maximum power density is reached earlier because the VMTB-μDMFC exhibits significant mass transfer resistance, making it difficult for the relatively low concentration of 5M methanol solution to meet the mass transfer requirements of the anode under high current discharge due to its concentration diffusion rate. Near the maximum power current density at 5M, the output voltage is rapidly increased. This also reflects insufficient methanol diffusion, leading to polarization in the later stages dominated by concentration polarization. At 9M, 11M, or higher concentrations, although the anode methanol diffusion rate is improved and anode concentration polarization is reduced, severe methanol infiltration hinders the cathode reaction. This results in a significant power drop, with the limiting current density at 11M decreasing to 100 mA / cm². 2 Therefore, the optimal operating concentration for this configuration at room temperature (298 K) is 7 M, which is consistent with previous simulation results. At this concentration, a good balance can be achieved between methanol diffusion and mass transfer at the anode and methanol permeation at the cathode.
[0100] Polarization curves and output performance were tested for both the traditional configuration and the VMTB-μDMFC at room temperature (298 K) and high temperature (333 K). Figure 10 (a) shows the test results at room temperature (298 K). The traditional μDMFC can achieve 18.84 mW / cm² under optimal operating conditions (2 M). 2 Its maximum output power is [value missing], however, under high-concentration fuel conditions (7M), accompanied by methanol permeation, the power drops sharply. Its maximum power density is 10.86 mW / cm³. 2 Only 58% of the previous level was achieved. VMTB-μDMFC, thanks to its excellent methanol barrier properties, still achieved 16.92 mW / cm² under 7M conditions. 2 The power density of VMTB-μDMFC is up to 56% higher at high concentrations compared to traditional μDMFC. However, under 2M conditions, due to insufficient methanol diffusion supply, the maximum power density of VMTB-μDMFC is only 9.88 mW / cm³. 2 This indicates that its special structure can have a large anodic mass transfer resistance at room temperature, making it unsuitable for operation under low concentration conditions.
[0101] Figure 10 (b) shows the test results at 333 K, where activation polarization decreases significantly with a substantial increase in catalyst activity. Since the diffusion coefficient of methanol in solution is described by Arrhenius-type equations, the diffusion coefficient increases significantly at high temperatures, and methanol permeation intensifies with this increase. Traditional μDMFCs, with their high catalyst activity at high temperatures, can achieve a power density of 37.2 mW / cm² at a 2 M concentration. 2Due to the dramatic increase in diffusion coefficient at high temperatures, the characteristics of VMTB-μDMFC, which were unsuitable for low-concentration methanol operation, have been significantly improved. VMTB-μDMFC can achieve 32.22 mW / cm² in 2M methanol solution operation. 2 The maximum power density and output performance at low concentrations are similar to those of conventional μDMFCs. However, methanol permeation intensifies at high temperatures, and at a high concentration of 7M, conventional μDMFCs without mass transfer barriers exhibit significant performance losses. Even with a substantial increase in catalyst activity, the maximum power density is only 8.21 mW / cm³. 2 The power density loss is as high as 28.99 mW / cm³. 2 The limiting current density can only be maintained at 100 mA / cm². 2 Nearby, the VMTB-μDMFC, aided by its mass transfer barrier layer and high catalyst activity, achieves a maximum power density of 15.07 mW / cm². 2 Compared to normal temperature operating conditions, the power consumption decreased by only 1.86 mW / cm². 2 Its performance is 83.5% higher than that of traditional μDMFC, with a limiting current density of 160 mA / cm². 2 .
[0102] VMTB-μDMFC and conventional μDMFC were placed in a constant temperature environment of 298K, and 1 mL of fuel with the methanol concentration corresponding to their respective optimal power was added. At 80 mA / cm² 2 The battery was discharged at high current density for an extended period to test its stability and battery life. The results are as follows: Figure 11 Although the voltage of the traditional μDMFC battery was higher than that of the VMTB-μDMFC in the initial stage of discharge, the discharge voltage continued to decrease as methanol was consumed, falling below the voltage of the traditional VMTB-μDMFC after 53 minutes. The higher specific energy of the high-concentration fuel meant that the voltage of the VMTB-μDMFC hardly decreased during the subsequent 3 hours of discharge. The final discharge duration was 283 minutes, a 148% increase compared to the 114 minutes of the traditional μDMFC.
[0103] AC impedance spectroscopy test
[0104] At room temperature (7 M), the fuel cell was subjected to constant current discharge using an electronic load, which was then used in conjunction with an electrochemical workstation for AC impedance spectroscopy (EIS) testing. The EIS was able to scan both cell configurations separately, maintaining the system discharge at 20 mA / cm². 2 Low current discharge region and 80mA / cm 2 The internal resistance in the high-current discharge region is analyzed, and the results are converted into a Nyquist plot as shown below. Figure 7 As shown. The low-current discharge region is... Figure 12(a). As can be seen from the figure, VMTB-μDMFC has a smaller radius of curvature at high concentrations, which means it has lower internal resistance. Figure 12 (b) shows the impedance spectrum in the high-current discharge region. Due to the reduction in the activation energy barrier, the overall arc radius is smaller than that under the low-current discharge condition, but the arc radius of VMTB-μDMFC still shows a trend of being smaller than that of traditional μDMFC.
[0105] To further investigate the internal resistance of the battery, ZView software was used to fit the AC impedance test results. From the EIS spectrum, it can be roughly observed that the impedance curve at high μDMFC concentration is composed of two arcs of different sizes. Therefore, two sets of LC circuits connected in series are used to approximate the two arc segments. The equivalent circuit model is as follows: Figure 13 As shown.
[0106] Among them, R ohm R is the charge transfer impedance, used to characterize charge transfer in solution and the contact resistance of internal components. A R C The unipolar internal resistance of the anode and cathode primarily characterizes the charge resistance resulting from the Faraday process. Since the μDMFC electrode interface is not an ideally smooth electrode plane, a constant-phase element (CPE) is used. A CPE C The non-Radar impedance is constructed to replace the ideal capacitor C, thus characterizing the single-layer interface capacitance. The anodic reaction involves a multi-step dehydrogenation oxidation reaction with relatively high internal resistance, but the adsorption and desorption rates of intermediate products in solution are extremely fast. Therefore, the reaction steps are relatively rapid, mainly responding to the high-frequency range. The adsorption and desorption rates of the reactants O2, products H2O, and secondary products H2O2 of the cathode oxygen reduction reaction on the electrode surface are relatively low. This will respond to the mid-frequency range of the impedance spectrum, corresponding to the right half-circle of the spectrum. After fitting the EIS spectrum, the simulation curve of the equivalent circuit is in Figure 12 The parameters are marked with thin lines, and the fitting results of each component parameter are shown in Table 1.
[0107] Table 2 EIS Test Equivalent Circuit Fitting Results
[0108]
[0109] Comparing the fitting results in Table 2, the cathode R of VMTB-μDMFC in the low current region C The methanol concentration is smaller than that of a traditional μDMFC due to reduced methanol permeation and decreased cathode polarization. In the high-current discharge range, after the slower methanol mass transfer at the anode and the faster methanol consumption in the VMTB-μDMFC reach equilibrium, less methanol solution permeates to the cathode compared to low-current discharge. This provides more three-phase interfaces for the reduction reaction, which is more conducive to the reaction. At this point, although R... ASlightly larger than a traditional μDMFC, but thanks to its smaller R C The total internal resistance is still lower than that of traditional μDMFC.
[0110] Methanol permeation linear scan
[0111] The AC impedance spectroscopy results showed that the difference in internal resistance between VMTB-μDMFC and traditional μDMFC mainly lies in the cathode. Therefore, linear sweep voltammetry (LSV) was performed on the methanol permeated into the cathode using an electrochemical workstation. High-concentration humidified N2 was introduced into the cathode. During the test, the working electrode was the cathode, while the reference and counter electrodes were connected to the anode. The scan rate was set to 5 mV / s. The following reactions occurred when the methanol-water solution permeated into the cathode:
[0112] CH3OH + H2O → CO2 + 6H+ + +6e - (7)
[0113] The reaction measured at the anodic anode is:
[0114] 6H + +6e - →3H2 (8)
[0115] The peak value of the scan curve can characterize the rate at which methanol permeates into the cathode.
[0116] Figure 14 The LSV scan curves for methanol permeation of VMTB-μDMFC and conventional μDMFC at 298 K and 333 K are shown. The scan results indicate that the peak value of VMTB-μDMFC at room temperature is 214.6 mA / cm². 2 Lower than the traditional μDMFC's 326.4 mA / cm 2 At high temperatures, permeation intensifies as the methanol diffusion coefficient changes. The peak values of the curves are generally higher than at low temperatures, but the peak value of VMTB-μDMFC is 456.6 mA / cm². 2 It is still lower than the peak value of the curve of traditional μDMFC, which is 641.1 mA / cm. 2 This fully demonstrates that the mass transfer barrier layer effectively reduces the permeation of methanol into the cathode in VMTB-μDMFC.
[0117] In summary, methanol permeation is the main factor limiting the output performance of μDMFC at high fuel concentrations. Finite element simulation analysis revealed that the VMTB-Layer can vertically widen the concentration gradient, reduce methanol permeation, and maintain the electrocatalysis at a reasonable concentration environment. SEM scanning of the surface morphology of the SSFF fibers after chemical etching showed that etching formed a concave-platform microstructure on the fiber surface, significantly increasing roughness. The treated SSFF exhibited strong capillary pressure and a high permeability coefficient, enabling it to act as the VMTB-Layer to rapidly transfer methanol solution to the high-level MEA diffusion layer. Comparative testing of the output performance of VMTB-μDMFC and conventional μDMFC showed that, compared to the conventional configuration, the VMTB-μDMFC increased the optimal fuel concentration from 2M to 7M at 298K, resulting in a 56% increase in power density. At 333K, the output power was 83% higher than that of the conventional μDMFC under 7M fuel conditions. At room temperature, a unit volume of 7M fuel increased the discharge duration by 148%. The results of fitting AC impedance spectroscopy measurements show that VMTB-μDMFC exhibits lower cathode internal resistance at high concentrations. Methanol permeation linear scan tests also confirm that the methanol permeation rate of VMTB-μDMFC is lower than that of traditional μDMFC under both room temperature and high temperature conditions. In summary, the excellent mass transfer barrier properties of VMTB-Layer can create a concentration gradient for VMTB-μDMFC under high concentration conditions, reducing methanol permeation, minimizing cathode polarization, and significantly improving the output performance and runtime of VMTB-μDMFC.
[0118] In the above-described practical examples, the materials and dimensions of the anode plate, sealing gasket, and cathode plate are all of conventional design. The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the technical scope disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer, comprising an anode plate (1) and a cathode plate (7) as clamps, characterized in that, The anode end plate (1) has a liquid storage chamber (8) located below the interior. One side of the liquid storage chamber (8) is sealed by a longitudinal mass transfer barrier layer (2) and an anode sealing gasket (3). The longitudinal mass transfer barrier layer (2) is embedded in one side of the anode sealing gasket (3) and contacts the MEA (4). The other side of the MEA (4) contacts the cathode current collector (6) through the cathode sealing gasket (5). The cathode sealing gasket (5) and the cathode current collector (6) are provided with a cathode end plate (7) on their exterior. The longitudinal mass transfer barrier layer (2) is made of stainless steel fiber felt material with a porosity of 70%-90%. The stainless steel fiber felt conducts the methanol solution from the storage chamber (8) below one side to the anode diffusion layer of MEA (4) above the other side through capillary pressure difference. The surface of the stainless steel fiber felt is chemically etched to form a microstructure, which improves the surface roughness. The process is as follows: the stainless steel fiber felt is immersed in a mixed solution of CuCl2 and HCl and reacted at 45-55℃ for 25-35 seconds. Then, it is immediately ultrasonically cleaned for 10-20 minutes to remove the Cu deposited on the fiber surface, and then dried in a constant temperature oven.
2. The high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer according to claim 1, characterized in that, The anode sealing gasket (3) has a cuboid frame in the middle. A longitudinal mass transfer barrier layer (2) is embedded on one side of the cuboid frame, and an anode diffusion layer of MEA (4) is embedded on the other side of the cuboid frame. The anode diffusion layer of MEA (4) is in contact with the longitudinal mass transfer barrier layer (2).
3. The high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer according to claim 1, characterized in that, The liquid storage chamber (8) is connected to a fuel filling channel (9), the opening of which is located above the anode plate (1).
4. The high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer according to claim 1, characterized in that, The MEA (4) has a proton exchange membrane in the middle, an anode diffusion layer on the left and a cathode diffusion layer on the right. The anode diffusion layer is coated with an anode catalyst on the side close to the proton exchange membrane, and the cathode diffusion layer is coated with a cathode catalyst on the side close to the proton exchange membrane.
5. The high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer according to claim 1, characterized in that, The cathode current collector (6) is a 304 stainless steel current collector with an opening ratio of 38.5%.
6. The high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer according to claim 1, characterized in that, The methanol fuel cell has a fuel concentration of 5-8 M.
7. The high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer according to claim 1, characterized in that, The lower edge of the anode diffusion layer of the MEA (4) is 3-10 mm away from the upper edge of the liquid storage cavity (8); the width of the longitudinal mass transfer barrier layer (2) is the same as the width of the MEA (4).
8. The high-concentration micro direct methanol fuel cell with a longitudinal mass transfer barrier layer according to claim 1, characterized in that, The bottom end of the longitudinal mass transfer barrier layer (2) coincides with the lower edge of the liquid storage cavity (8), and the top end is 3-10 mm higher than the top end of the anode plate (1).
Citation Information
Patent Citations
Surface roughening treatment method for stainless steel
CN107747096A
Fuel supply device for direct methanol fuel cells
US20050069736A1